Behavior Collapse Investigation of A Steel Sheet Pile with LISA FEA V8 - Wahyudi Efendi, ST., MT., ASEAN Eng., ACPE., APEC Eng., Ir. Aco (SAINSTECH NUSANTARA, 2025)
The collapse of the Tank Area embankment led to the failure of the steel sheet pile installed on the west side of the planned position. Evidence suggested that the installation process of the sheet pile induced vibrations, which may have contributed to the failure. This study aimed to investigate the actual behavior of the failure through reverse analysis and finite element modeling techniques. These analyses helped identify the causes of the failure and provided reinforcement recommendations for improving the current condition. The findings revealed that the existing state, when evaluated with the current soil parameters, was prone to failure. During the land clearing process, a slip plane formed, resulting in a safety factor (SF) of 0.036. Despite the installation of the sheet pile, the condition continued to deteriorate due to significant lateral soil pressures, causing the sheet pile to collapse. However, when the SF increased to 1.431, which exceeds the necessary SF of 1.2, the stability of the sheet pile improved, and the value approached a stable limit of 0.984. Based on these findings, recommendations are made to enhance the stability and prevent further risks and deterioration.